Organizational Conflict Model in Managing Indigenous Papuans Local Economic Development: A Case Study of Jayapura - Anggraini, Lya; Maksum, Irfan Ridwan; Halidin, Hardin (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2019)
The Mayor of Jayapura City is leading the city to be religious, advanced, modern, prosperous, and uphold local wisdom. As the capital of Papua Province, this city faces a prolonged problem of inequality from within the city, with the province of West Papua, and neighboring Papua New Guinea. The paper questions how Jayapura City, as the capital of Papua Province manages inequalities and drive the economic sector forward based on the Organizational Conflict Model of Pondy (1967). Results of in-depth interview and secondary data research were analyzed based on qualitative analysis. Inequalities have hit indigenous Papuans the hardest. They are also facing the pressure of higher skilled settlers from other parts of Indonesia and encroachment from the indigenous mountain Papuans. Based on the model, we have found that the Mayor has been responsive to mitigate potential conflicts. The bureaucracy is supported by the military, police, community leaders, and academics. We argue that representative bureaucracy taking into account customary law and indigenous beliefs will reduce tension in the society and receive support in program implementation of the city.